Forms and methods of formation of auditory self-control skills of the future art school teacher in instrumental ensemble classes - Isaіenko Наnnа (Науковий Вісник Південноукраїнського Національного Педагогічного Університету імені К. Д. Ушинського)
The article defines the forms and means of forming auditory self-control skills of the future art school teacher in instrumental ensemble classes. The purpose and objectives of this research are formulated. The scientific literature is analyzed, which presents the works of scientists who determine the forms of organization of musical and professional training in institutions of higher education. The concept of “form of educational organization” is characterized. Among the defined forms of formation of auditory self-control skills of a future art school teacher in instrumental ensemble classes, we included a group form of work, which involves a creative workshop divided into full and micro groups, where students acquire various professional skills and abilities and develop auditory self-control skills. And to the means of forming the skills of auditory self-control of the future art school teacher in instrumental ensemble classes, we included: combined means of communication that combine verbal and non-verbal communication, simultaneous use of voice, mime and gestural display, illustrative display and information; musical and technical, namely various musical instruments. It was also noted that the discipline “Instrumental Ensemble”is included in the course of special disciplines. The content of which embodies the main tasks of developing the performing ensemble abilities of the future teacher of the art school and contains the following components: theoretical, practical, independent work of students. Ensemble music-making is a creative form of interaction of ensemble members, their communication is the most perfect means of personal development of a professional. We believe that the forms and means of forming auditory self-control skills of the future art school teacher in instrumental ensemble classes contribute to the effective formation of this phenomenon.